Evidence on methylphenidate in children and adolescents with ADHD is in fact of 'very low quality'. Issue 4 (8th October 2016) - Storebø, O J; Zwi, M; Krogh, H B; Moreira-Maia, C R; Holmskov, M; Gillies, D; Groth, C; Simonsen, E; Gluud, C
Abstract : Banaschewski and colleagues from the European Attention Deficit Hyperactivity Disorder (ADHD) guideline group make a number of critical comments regarding our systematic review on methylphenidate for children and adolescents with ADHD. In this article, we present our views, showing that our trial selection was not flawed and was undertaken with scientific justification. Similarly, our data collection and interpretation was systematic and correct. We have followed a sound methodology for assessing risk of bias and our conclusions are not misleading. We acknowledge that different researchers might make risk of bias judgments at higher or lower thresholds, but we have been consistent and transparent in applying our pre-defined and per reviewed protocol. Although we made minor errors, we demonstrate that the effects are negligible and not affecting our conclusions. We are happy to correct such errors and to engage in debate on methodological and ethical issues. In terms of clinical implications, we are advocating that clinicians, patients and their relatives should weight carefully risks and benefits of methylphenidate. Clinical experience seems to suggest that there are people who benefit from this medication. Our systematic review does, however, raise questions regarding the overall quality of the methylphenidate trials.